Controlling astroturfing on the internet: a survey on detection techniques and research challenges. (6th May 2019) - Mahbub, Syed; Pardede, Eric; Kayes, A.S.M.; Rahayu, Wenny
Astroturfing is one of the most impactful threats on today's internet. It is the process of masking and portraying a doctored message to the general population in a way as though it originated from the grass-root level. The concept of astroturfing detection is started to gain popularity among researchers in social media, e-commerce and politics. With the recent growth of crowdsourcing systems, astroturfing is also creating a profound impact on people's opinions. Political blogs, news portals and review websites are being flooded with astroturfs. Some groups are using astroturfing to promote their interest and some are using it to demote the interest of competitors. Researchers have adopted many approaches to detect astroturfing on the web. These approaches include content analysis techniques, individual and group identification techniques, analysing linguistic features, authorship attribution techniques, machine learning and so on. We present a taxonomy of these approaches based on the key issues in online astroturfing detection techniques and discuss the relevant approaches in each category . The paper also summarises the discussed literature and highlights research challenges and directions for future work that have not aligned with the currently available research.